Neutrophilic Dermatosis in Myelodysplastic Syndrome and Chronic Active Hepatitis C - Rupam Sharma MD; Royce H. Johnson MD; Arash Heidari MD; Matthew Malerich MD; William R. Stull MD; Everardo Cobos MD (SAGE Publishing, 2021)
In this article, we describe a case of neutrophilic dermatosis of the dorsal hands (NDDH) complicated with myelodysplastic syndrome and chronic active hepatitis C infection. NDDH was first suggested by Galaria et al in 2000. After comparing features of NDDH with Sweet syndrome in terms of encompassing clinical, laboratory, and histological characteristics, it can be concluded that "distributional or localized variant" of Sweet syndrome is classified as NDDH. Early diagnosis and treatment can improve prognosis. Systemic glucocorticoids are the mainstay of treatment.